MANAJEMEN PEMBELAJARAN PAI DALAM IMPLEMENTASI MULTIKULTURALISME KEPADA SISWA DI SMA 1 BADAR ACEH TENGGARA - Sari Pitri; Elvi Khairiah; Safriadi (FITRAH: International Islamic Education Journal, 2023)
Ethnic and cultural differences in the same educational environment are commonplace for students at SMA 1 Badar, various ethnic groups belonging to students such as Alas, Gayo, Malay, Batak, and others join in the implementation of PAI learning, each tribe has characteristics, background and character, different, resulting in conflict between one another. In overcoming these differences PAI teachers implement multicultural attitudes to students through PAI learning and teachers plan, implement, and evaluate these attitudes to students in the PAI learning process. The aim of this research is to determine PAI learning management in implementing multiculturalism for students. The research method used was a descriptive qualitative method using observation, interview and documentation data collection techniques. The results of this research are that PAI teachers implement an attitude of multiculturalism and organize planning, implementation, and evaluation. This attitude includes an attitude of tolerance, an attitude of mutual help, an attitude of equality, an attitude of cooperation, and an attitude of prioritizing language/prayer.